Ultrasound Guidance Combined with C-Arm Fluoroscopy in Selective Semilunar Ganglion Radiofrequency Thermocoagulation Through the Foramen Ovale for Trigeminal Neuralgia: A Randomized Controlled Trial. Issue 4 (19th September 2022) - Liang, Hui; Guo, Yuna; Chen, Guoqing; Zhao, Xiaojing; Dou, Zhi; Sun, Fenglong; Yu, Dejun; Lin, Zengmao; Zhang, Feng; Liu, Xiufen; Wu, Baishan; Ni, Jiaxiang
Abstract: Objective: To explore the clinical value of ultrasound guidance combined with C-arm guidance during selective semilunar ganglion radiofrequency thermocoagulation via the foramen ovale for trigeminal neuralgia. Methods: This study enrolled 48 patients diagnosed with trigeminal neuralgia between January 2021 and December 2021 in the Department of Pain Management at Xuanwu Hospital. Patients were randomly and equally divided into a C-arm–only group and an ultrasound-combined-with–C-arm (ultrasound+C-arm) group, according to a random number table. After exclusions, 42 patients were analyzed. Of these, 21 patients underwent selective semilunar ganglion radiofrequency thermocoagulation via the foramen ovale guided by the C-arm alone, whereas 21 patients underwent the same procedure guided by ultrasound combined with C-arm. The number of punctures, the amount of time elapsed until the target area of the semilunar ganglion was punctured, the cumulative dose of radiation exposure, and puncture-related complications were recorded during the operation. Numerical rating scale scores and radiofrequency thermocoagulation–related complications were evaluated preoperatively and at 1 day, 3 days, 7 days, 1 month, and 3 months after surgery. Results: The number of punctures, the amount of time elapsed until the target area of the semilunar ganglion was punctured, and the cumulative dose of radiation exposure were all lower in the ultrasound+C-arm group than in the C-arm–only group (all P  < 0.05). No significant differences were found in numerical rating scale scores and radiofrequency thermocoagulation–related complications between the two groups ( P  > 0.05). No puncture-related complications occurred in either of the groups. Conclusion: Ultrasound guidance combined with C-arm guidance could be safely used for puncturing the semilunar ganglion via the foramen ovale, with more efficiency and less radiation exposure than C-arm guidance alone.